From Evidence to Practice: A Comprehensive Analysis of Side Effects in Synthetic Anti-Depressant Therapy - Pannu, Arzoo; Goyal, Ramesh K. (Current Drug Safety, 2025)
Depression, a pervasive mental health disorder, affects millions worldwide, necessitating the widespread use of synthetic anti-depressant medications. While these pharmaceutical interventions have demonstrated efficacy in alleviating depressive symptoms, they are not without their associated side effects. This review provides a comprehensive overview of the side effects of synthetic anti-depressants, aiming to enhance the understanding of their clinical implications. Common side effects explored include gastrointestinal disturbances, sexual dysfunction, insomnia, weight gain, and cognitive impairments. Additionally, this review delves into less frequent but potentially severe adverse events, such as serotonin syndrome, hyponatremia, and cardiac complications associated with specific classes of synthetic anti-depressants. Moreover, the review examines the interplay between side effects and treatment adherence, emphasizing the importance of monitoring and managing these effects in clinical practice. It also discusses strategies to mitigate side effects, including dose adjustments, combination therapy, and alternative treatment approaches. In conclusion, this comprehensive review sheds light on the multifaceted landscape of side effects associated with synthetic anti-depressants. By providing clinicians with a nuanced understanding of these effects, it aims to facilitate informed decision-making, personalized treatment plans, and improved patient outcomes in managing depression.
Keywords: Antidepressant medications